Prioritizing the Construction of Bicycle Lanes in the Central Area of Tehran Based on Sustainable Transportation Principles - Khashayar Mahmoudian; Amirhassan Kermanshah (مهندسی عمران شریف)
One of the sustainable solutions to alleviate existing issues caused by personal vehicle usage is the promotion of cycling. The initial step to increase public interest in cycling involves establishing suitable bike lanes. These lanes should not only be safe but also provide a comfortable, attractive environment while ensuring convenient access to public transportation stations and facilitating interaction with other modes of public transit. This research investigates three routes in Tehran's central area, aiming to prioritize them for bicycle lane construction based on safety, attractiveness, and movement potential criteria. Under the safety criterion, important sub-criteria include the slope of the route, permissible speed of vehicles in the lane, traffic volume, the number of intersections, and the location of congestion charge zones. These factors play a pivotal role in creating a secure cycling infrastructure. The attractiveness criterion takes into account sub-criteria such as land use diversity and the incorporation of green spaces along the routes, enhancing the overall cycling experience. Simultaneously, the movement potential criterion evaluates sub-criteria, including the resident population, the availability of public transport stations, and the proximity to educationalcenters. This ensures that the selected routes are not only safe and attractive but also practical within the urban context. In this study, the Analytical Hierarchy Process (AHP) is utilized to determine the importance of each parameter. The results indicate that sub-criteria such as the slope of the route, permissible speed of vehicles in the lane, and the number of intersections on the route are more important within the safety criterion. After prioritizing the routes for theconstruction of bicycle lanes based on the criteria and sub-criteria in this research, Shoosh Street is identified as having a higher priority compared to other streets. Following Shoosh Street,th 17 Shahrivar Street, and Ferdowsi Street are the next in line for constructing bicycle lanes.